Adenoid Ciliostimulation in Children with Chronic Otitis Media. Issue 1 (2nd October 2012) - Andreoli, Steven M.; Schlosser, Rodney J.; Wang, Ling‐Feng; Mulligan, Ryan M.; Discolo, Christopher M.; White, David R.
Abstract : Objective: Adenoid hypertrophy and chronic adenoiditis are associated with an increased incidence of chronic otitis media. This study intends to determine the relationship between chronic otitis media and dynamic ciliary beat frequency in children undergoing adenoidectomy. Study Design: Prospective, controlled study. Setting: Pediatric tertiary care hospital. Subjects and Methods: Children undergoing adenoidectomy were enrolled. Patients were stratified according to their indication for surgery, including adenotonsillar hypertrophy with obstructive sleep apnea, chronic otitis media with effusion, or recurrent episodes of acute otitis media. Adenoids were harvested using the curette. Tissue was sectioned and allowed to equilibrate in basal media for 24 hours. Cilia‐bearing tissue was then stimulated using isoproterenol or methacholine. Ciliary beat frequency was serially reordered and analyzed using the Sisson‐Ammons Video Analysis software program. Results: Baseline ciliary beat frequency was similar in all groups (N = 47, total). Using isoproterenol, children with chronic otitis media with effusion demonstrated a blunted dynamic ciliary response at 2 and 3 hours relative to control ( P =. 0176 and P =. 0282). Methacholine‐stimulated ciliary beat frequency was not different between each group. Conclusion: At 2 and 3 hours following isoproterenol stimulation, there was a significant blunting of dynamic ciliary beat frequency in children with chronic otitis media with effusion. This ciliary dysfunction may provide a physiological explanation related to chronic adenoiditis in children with chronic otitis media.